2012^2/2011^2+2013^2-2=(2012^2-2011^2)/2011^2+2013^2-1=(2012+2011)(2012-2011)/2011^2+(2013+1)(2013-1)=(2012+2011)/2011^2+2014*2012=4023/2011^2+2014*2012
利用因式分解计算2012^2/2011^2+2013^2-2
2个回答
相关问题
-
利用因式分解, 计算:2012²/2011²+2013²-2
-
利用因式分解计算:2012+2012^2-2013^2(要过程)
-
利用因式分解计算:2013^3-2*2013^2+2011分之2013^3+2*2013^2-2014
-
2012^2-2012*12=利用因式分解计算
-
简便计算:2013*2011-2012^2
-
利用乘法公式计算2013^2-2013x4024+2012^2
-
利用因式分解计算:2010²÷2009²+2011²-2
-
计算:(-2)^2013+(-2)^2012+(-2)^2011+…+(-2)^3+(-2)^2+(-2)+1
-
利用因式分解进行计算:2011²—2011×2012
-
(1)计算:2013^2-2012^2+2011^2-2010^2+2009^2-2008^2+2